The Relationship between Teachers’ Motivation, Professional Development, and Mobile Technology Integration in Language Learning - Pathan, Habibullah; Moskvitcheva, Svetlana Alekseevna; Khatoon, Sahib; Aleksandrova, Oksana Ivanovna (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study investigates the significance of professional development and teacher motivation in the effective utilization of mobile technology in language instruction. It explores how these variables have a significant impact on the adoption and utilization of technological tools in language teaching. The study investigates the relationship between teachers’ motivation and the importance of comprehensive professional development programs that encompass pedagogical approaches and proficiency in mobile technology. The study followed a mixed-method research design with a sample of (n = 200) teachers and students. The results underscore the importance of a synergistic connection between professional development, technological integration, and teacher motivation to enhance language learning in digital learning environments. The study recommends that through targeted professional development and motivational tactics, curriculum designers and educators can optimize language instruction.